Automotive grade ultra-long durable antibacterial varnish, preparation method and application

By using compound hydroxy resin, nano-micro powder and additives in automotive grade varnish, combined with nanohybrid inorganic antibacterial materials and organic antibacterial agents, a synergistic coating is formed, which solves the problem of automotive grade ultra-long durable antibacterial varnish Performance and long-term effectiveness issues have achieved efficient sterilization and long-term antibacterial effects.

CN118909533BActive Publication Date: 2025-02-25DAHAN TECH (CHANGXING) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411406448.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-02-25
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The prior art cannot provide automotive-grade ultra-long durable antibacterial varnish, especially lacking systematic research on coating performance and antibacterial long-term performance.

Method used

By using compound hydroxy resin, nano-micro powder and a series of additives, combined with nano-hybrid inorganic antibacterial materials and ammonium organic antibacterial agents, a synergistic coating is formed to meet the technical requirements of automotive-grade interior coatings.

Benefits of technology

It has achieved the efficient bactericidal effect and antibacterial long-term antibacterial varnish of automotive grade. The coating has no obvious attenuation under high and low temperature aging, photoaging and other conditions, and has good aging resistance and decorative effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118909533B_ABST
    Figure CN118909533B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of production and manufacturing of automotive-grade varnish, and specifically to an automotive-grade ultra-long-lasting antibacterial varnish, a preparation method and an application thereof. The coating meets the technical requirements of automotive-grade interior coatings by adopting a compounded hydroxyl resin, nano-powder and a series of additives. Nano-hybrid inorganic antibacterial materials and ammonium salt organic antibacterial agents are added, and the organic and inorganic antibacterial agents can act synergistically in the coating. The varnish coating meets the performance requirements of automotive-grade coatings and has an extremely high antibacterial rate and an extremely low antibacterial rate aging attenuation. The varnish coating has an excellent antibacterial effect before aging, and the killing rates of Escherichia coli, Staphylococcus aureus and Candida albicans are greater than 99.99%. After 20 cycles of high and low temperature aging and more than 800 hours of light aging, the antibacterial effect has no obvious attenuation, and the killing rates of Escherichia coli, Staphylococcus aureus and Candida albicans are greater than 99.99%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of production and manufacturing of automotive-grade varnish, and in particular to an automotive-grade ultra-long-lasting antibacterial varnish, a preparation method and application thereof. Background Art

[0002] Varnishes are generally classified into consumer grade, industrial grade, and automotive grade from low to high according to the durability and reliability performance of components. Existing antibacterial varnishes are mainly consumer grade products with low performance requirements, such as wood antibacterial varnish, color plate antibacterial varnish, etc., which are used on the surfaces of furniture wood, color steel plates, etc., and have certain antibacterial and decorative effects. Antibacterial varnish is almost completely transparent, does not change the color of the object itself, and has a strong decorative effect. At present, for automotive grade antibacterial varnish products, there is no systematic research on the coating performance and long-term antibacterial performance of such products on the market.

[0003] The current research on automotive-grade varnish, such as a varnish suitable for one-time spray film formation on a car body and a preparation method thereof disclosed in CN202210615954.8, targets the problems of sag and prickly heat spots after the varnish is sprayed on the car body, but does not study the long-term antibacterial effect of the varnish.

[0004] For another example, CN202010861629.0 discloses a varnish coating for automobile bodies and its application, which contains: component a, the preparation process of which includes: in the presence of a polymerization catalyst, pentanediol, hexanediol and dimethyl carbonate are polymerized, and then the resulting reaction mixture is subjected to an ester exchange reaction with polyoxytetramethylene glycol; component b, the preparation process of which includes: in the presence of an organic solvent and a polymerization initiator, 2-hydroxypropyl acrylate, styrene and isobutyl methacrylate are polymerized; component c, a polyisocyanate compound; component d, butyl acetate and an aromatic hydrocarbon fraction with a boiling point of 158-172°C. The varnish coating according to the present invention has good abrasion resistance while having high adhesion and hardness, but the technical solution does not study the long-term antibacterial effect of the varnish.

[0005] Therefore, there is an urgent need for an automotive-grade, ultra-long-lasting antibacterial varnish. Summary of the invention

[0006] In view of the problem that existing varnishes cannot achieve the ultra-long-lasting antibacterial performance of automotive grade, the purpose of the present invention is to provide an automotive grade high-performance antibacterial varnish, preparation method and application that surpasses the general industrial grade and has ultra-long durability. By using compounded hydroxyl resin, nano-powder and a series of additives, the coating meets the technical requirements of automotive grade interior coatings, and nano-hybrid inorganic antibacterial materials and ammonium salt organic antibacterial agents are added, and the organic and inorganic antibacterial agents can work synergistically in the coating. The varnish coating meets the performance requirements of automotive grade coatings, and at the same time has extremely high antibacterial rate and extremely low antibacterial rate aging attenuation.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] An automotive grade ultra-long durable antibacterial varnish, comprising:

[0009] Component A, component B and component C, the ratio of component A, component B and component C is (A+B): C=1:0.4-0.7, where A:B=10:3;

[0010] In parts by weight, the component A includes 40-75 parts of mixed hydroxyl resin, 10-25 parts of mixed solvent, 1-3 parts of additives, 1-3 parts of nano antibacterial micropowder, 0.5-3 parts of surface modified micropowder and 0.2-1 parts of rheological additive, totaling 100 parts;

[0011] In parts by weight, the component B includes 60-80 parts of a mixed polyisocyanate curing agent and 20-40 parts of n-butyl acetate, a total of 100 parts;

[0012] The C component is a diluent, which is a mixture of multiple solvents. Its function is to provide a coating system with an optimal volatilization gradient through the combination of different solvents and the coordination with the solvent in the A component, so that it has better construction performance and surface effect. By weight, the C component includes 5-20 parts of ethyl acetate, 5-20 parts of n-butyl acetate, 10-25 parts of propylene glycol methyl ether acetate, 20-40 parts of high boiling point aromatic solvent oil and 5-20 parts of mixed dibasic acid esters, totaling 100 parts.

[0013] As an improvement, in the component A, the mixed hydroxyl resin is a mixture of hydroxyl acrylic resin and hydroxyl polyester resin, the weight fraction of the hydroxyl acrylic resin in the mixed hydroxyl resin is 80-90%, and the weight fraction of the hydroxyl polyester resin in the mixed hydroxyl resin is 10-20%, wherein the hydroxyl acrylic resin in the mixed hydroxyl resin serves as the film-forming body, providing fast drying and basic properties, and the polyester resin serves as a modified resin, providing toughness and impact resistance.

[0014] As an improvement, in the component A, the mixed solvent is a mixture of n-butyl acetate, propylene glycol methyl ether acetate and ethylene glycol butyl ether acetate, the weight fraction of n-butyl acetate in the mixed solvent is 20-30%, the weight fraction of propylene glycol methyl ether acetate in the mixed solvent is 30-50%, and the weight fraction of ethylene glycol butyl ether acetate in the mixed solvent is 20-30%;

[0015] The mixed solvent is used to provide a suitable volatilization gradient and excellent dissolving power.

[0016] As an improvement, in the component A, the auxiliary agent includes a mixture of a leveling agent, an anti-ultraviolet auxiliary agent and a polyurethane drying agent;

[0017] The leveling agent comprises a polyacrylate leveling agent and a polyether-modified silicone leveling agent, wherein the weight fraction of the polyacrylate leveling agent in the auxiliary agent is 10-20%, and the weight fraction of the polyether-modified silicone leveling agent in the auxiliary agent is 5-10%. The two leveling agents provide short-wave leveling and long-wave leveling of the paint surface, prevent fisheyes and shrinkage craters in the paint film, and improve the leveling effect of the paint film;

[0018] The anti-ultraviolet additive comprises one or more of a benzotriazole light stabilizer, a piperidine light stabilizer and a hydroxytriazine derivative ultraviolet absorber, wherein the weight fraction of the anti-ultraviolet additive in the additive is 60-80%, and the two ultraviolet absorbers and a hindered amine stabilizer function to shield and absorb ultraviolet rays and capture harmful free radicals;

[0019] The polyurethane drying agent is bismuth octanoate drying agent, and its weight fraction in the auxiliary agent is 5-10%.

[0020] As an improvement, in the component A, the nano antibacterial micropowder is silver ion hybridized nano zinc oxide, wherein the nano antibacterial micropowder is an inorganic nano antibacterial material, the inorganic antibacterial material has excellent aging stability, the doped structure helps to improve the antibacterial effect, the special morphology design helps to stabilize dispersion and increase specific surface area, and also helps to improve the antibacterial rate.

[0021] The specific preparation method of silver ion hybrid nano zinc oxide is as follows:

[0022] Step T1, 7-15% Zn(NCS)2(C5H5N)2, 70-85% deionized water, 3-8% ammonia water and 0.5-1% supramolecular anchoring agent are mixed and reacted at 160-220°C for 4-12h to prepare nano ZnO by a hydrothermal method, wherein the supramolecular anchoring agent is preferably a polyetheramine supramolecular anchoring agent;

[0023] Step T2, washing the nano ZnO prepared in step T1 with deionized water and performing ultrasonic depolymerization for 4-8 times, and drying at 120° C. for 2-4 hours to obtain nano ZnO powder;

[0024] Step T3, allowing the silver nitrate solution to react with the alkali solution for 24 hours to obtain a nanosilver precursor;

[0025] Step T4, washing the nanosilver precursor prepared in step T3 with deionized water and ultrasonic depolymerization for 4-8 times, and drying at 00° C. for 4-8 hours to obtain a nanosilver precursor;

[0026] Step T5, mixing the nano ZnO powder obtained in step T2 with the nano silver precursor obtained in step T4, wherein the nano silver precursor accounts for 0.5-5%, grinding after mixing, and reacting at 500-800° C. for 2-6 hours, then cooling and grinding into ultrafine powder to form silver ion hybrid nano zinc oxide.

[0027] As an improvement, in the A component, the surface modified micropowder is a mixture of polyethylene wax powder and polyfluorine modified wax powder, the weight fraction of the polyethylene wax powder in the surface modified micropowder is 50-80%, and the weight fraction of the polyfluorine modified wax powder in the surface modified micropowder is 20-50%. The surface modified micropowder improves the smoothness of the paint film and has a good effect on improving scratch resistance, wear resistance, and resistance to cosmetics wiping.

[0028] As an improvement, in the component A, the rheological additive is a polyethylene wax with a transparency of more than 80%. The high-transparency polyethylene wax prevents powder sedimentation while not significantly affecting the light transmittance and decorative effect of the paint film.

[0029] As an improvement, in the B component, the mixed polyisocyanate curing agent is a mixture of HDI trimer and IPDI trimer, the weight fraction of the HDI trimer in the mixed polyisocyanate curing agent is 30-50%, and the weight fraction of the IPDI trimer in the mixed polyisocyanate curing agent is 50-80%. The HDI trimer and IPDI trimer mixed polyisocyanate curing agent can improve the curing speed and yellowing resistance, and the addition of IPDI trimer improves the hardness, chemical resistance and water resistance of the paint film.

[0030] In addition, the present invention also provides a method for preparing the above-mentioned automotive grade ultra-long durable antibacterial varnish.

[0031] The preparation method of component A is as follows:

[0032] Step S1, adding a mixed hydroxy resin, a mixed solvent, an additive, a nano antibacterial powder, a surface modified powder and a rheological additive in order according to a ratio, and stirring continuously for 5 minutes at a rotation speed of 200-400 rpm;

[0033] Step S2, grinding the mixed liquid stirred in step S1 by a nano sand mill for about 1 hour, the grinding medium particle size of the nano sand mill is 0.5 mm, and the fineness of the material after grinding is less than 10 μm;

[0034] Step S3, filtering the ground material in step S2 through a 400-mesh filter and then canning to obtain component A;

[0035] The preparation method of component B is as follows:

[0036] Add the mixed polyisocyanate curing agent and n-butyl acetate in order according to the ratio, and stir at a speed of 200-400 rpm for 10 minutes to obtain component B.

[0037] Furthermore, the present invention also provides an application of the above-mentioned automotive-grade ultra-long-lasting antibacterial varnish.

[0038] Add component B to component A in proportion, add the diluent of component C in proportion, spray it onto the surface of the object with an air spray gun, and dry it naturally for 7 days or bake it at 70℃ for 2 hours to completely cure, thereby obtaining an ultra-long-durable automotive-grade high-performance antibacterial coating.

[0039] The beneficial effects of the present invention are:

[0040] (1) The automotive-grade ultra-long-lasting antibacterial varnish of the present invention has a highly efficient bactericidal effect, and the automotive-grade ultra-long-lasting antibacterial varnish coating has an excellent antibacterial effect before aging. According to the detection method of GB / T21866, the killing rate of Escherichia coli, Staphylococcus aureus and Candida albicans is greater than 99.99%;

[0041] (2) The automotive-grade ultra-long-lasting antibacterial varnish of the present invention has ultra-durable antibacterial properties. After 20 cycles of high and low temperature aging and more than 800 hours of light aging, the antibacterial effect has no obvious attenuation. According to the detection method of GB / T21866, the killing rate of Escherichia coli, Staphylococcus aureus and Candida albicans is greater than 99.9%;

[0042] (3) The automotive-grade ultra-long-lasting antibacterial varnish of the present invention has good aging resistance, and the formed coating also has excellent heat aging resistance, condensation water resistance, light aging, high and low temperature aging resistance, chemical resistance and hand cream resistance;

[0043] (4) The automotive-grade ultra-long-lasting antibacterial varnish of the present invention has wear resistance. After 100 dry grindings, 100 wet grindings, and 2,000 special dry grindings, the coating has no visible changes or wear;

[0044] (5) The automotive-grade ultra-long-lasting antibacterial varnish of the present invention is a zero-odor product: the coating has an extremely low odor, reaching rating 1 "no odor";

[0045] (6) The automotive-grade ultra-long-lasting antibacterial varnish of the present invention has a decorative effect, the coating does not change the original surface color, the appearance is transparent, and the gloss reaches more than 90°.

[0046] In summary, the automotive-grade ultra-long durable antibacterial varnish of the present invention meets the performance requirements of automotive-grade coatings for various harsh environments, has passed tests such as high and low temperature alternation, light aging resistance, high temperature heat aging, condensation water test, hydrolysis resistance, etc., meets the wear resistance requirements of automotive-grade coatings, has passed dry grinding, wet grinding and special dry grinding tests, meets the tolerance requirements of automotive-grade interior coatings for many chemicals, has passed chemical resistance tests, perfume resistance tests, hand cream and sunscreen resistance tests, has high antibacterial rate and antibacterial durability, and both new coatings and aged coatings have extremely high antibacterial rates, which is particularly suitable for the technical field of automotive-grade ultra-long durable antibacterial varnish. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 The schematic diagram of the preparation process of the nano antibacterial powder of the present invention;

[0048] Figure 2 This is a microscopic image of the antibacterial test sample of the present invention before aging;

[0049] Figure 3 This is a microscopic picture of the antibacterial test sample of the present invention after high and low temperature aging;

[0050] Figure 4 This is a microscopic picture of the antibacterial test sample of the present invention after light aging. DETAILED DESCRIPTION

[0051] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0052] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present invention.

[0053] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0054] Example:

[0055] An automotive grade ultra-long durable antibacterial varnish, comprising:

[0056] Component A, component B and component C, the ratio of component A, component B and component C is (A+B): C=1:0.4-0.7, where A:B=10:3;

[0057] In parts by weight, the component A includes 40-75 parts of mixed hydroxyl resin, 10-25 parts of mixed solvent, 1-3 parts of additives, 1-3 parts of nano antibacterial micropowder, 0.5-3 parts of surface modified micropowder and 0.2-1 parts of rheological additive, totaling 100 parts;

[0058] In parts by weight, the component B includes 60-80 parts of a mixed polyisocyanate curing agent and 20-40 parts of n-butyl acetate, a total of 100 parts;

[0059] The C component is a diluent, which is a mixture of multiple solvents. Its function is to provide a coating system with an optimal volatilization gradient through the combination of different solvents and the coordination with the solvent in the A component, so that it has better construction performance and surface effect. By weight, the C component includes 5-20 parts of ethyl acetate, 5-20 parts of n-butyl acetate, 10-25 parts of propylene glycol methyl ether acetate, 20-40 parts of high boiling point aromatic solvent oil and 5-20 parts of mixed dibasic acid esters, totaling 100 parts.

[0060] Among them, in the component A, the mixed hydroxyl resin is a mixture of hydroxyl acrylic resin and hydroxyl polyester resin, the weight fraction of the hydroxyl acrylic resin in the mixed hydroxyl resin is 80-90%, and the weight fraction of the hydroxyl polyester resin in the mixed hydroxyl resin is 10-20%, wherein the hydroxyl acrylic resin in the mixed hydroxyl resin serves as the film-forming body to provide fast drying and basic properties, and the polyester resin serves as a modified resin to provide toughness and impact resistance.

[0061] Furthermore, in the component A, the mixed solvent is a mixture of n-butyl acetate, propylene glycol methyl ether acetate and ethylene glycol butyl ether acetate, wherein the weight fraction of n-butyl acetate in the mixed solvent is 20-30%, the weight fraction of propylene glycol methyl ether acetate in the mixed solvent is 30-50%, and the weight fraction of ethylene glycol butyl ether acetate in the mixed solvent is 20-30%;

[0062] The mixed solvent is used to provide a suitable volatilization gradient and excellent dissolving power.

[0063] Furthermore, in the component A, the auxiliary agent includes a mixture of a leveling agent, an anti-ultraviolet auxiliary agent and a polyurethane drying agent;

[0064] The leveling agent comprises a polyacrylate leveling agent and a polyether-modified silicone leveling agent, wherein the weight fraction of the polyacrylate leveling agent in the auxiliary agent is 10-20%, and the weight fraction of the polyether-modified silicone leveling agent in the auxiliary agent is 5-10%. The two leveling agents provide short-wave leveling and long-wave leveling of the paint surface, prevent fisheyes and shrinkage craters in the paint film, and improve the leveling effect of the paint film;

[0065] The anti-ultraviolet additive comprises one or more of a benzotriazole light stabilizer, a piperidine light stabilizer and a hydroxytriazine derivative ultraviolet absorber, wherein the weight fraction of the anti-ultraviolet additive in the additive is 60-80%, and the two ultraviolet absorbers and a hindered amine stabilizer function to shield and absorb ultraviolet rays and capture harmful free radicals;

[0066] The polyurethane drying agent is bismuth octanoate drying agent, and its weight fraction in the auxiliary agent is 5-10%.

[0067] In addition, in the component A, the nano antibacterial micropowder is silver ion hybrid nano zinc oxide, wherein the nano antibacterial micropowder is an inorganic nano antibacterial material, the inorganic antibacterial material has excellent aging stability, the doped structure helps to improve the antibacterial effect, the special morphology design helps to stabilize dispersion and increase the specific surface area, and also helps to improve the antibacterial rate.

[0068] like Figure 1As shown, the specific preparation method of silver ion hybrid nano zinc oxide is as follows:

[0069] Step T1, 7-15% Zn(NCS)2(C5H5N)2, 70-85% deionized water, 3-8% ammonia water and 0.5-1% supramolecular anchoring agent are mixed and reacted at 160-220°C for 4-12h to prepare nano ZnO by a hydrothermal method, wherein the supramolecular anchoring agent is preferably a polyetheramine supramolecular anchoring agent;

[0070] Step T2, washing the nano ZnO prepared in step T1 with deionized water and performing ultrasonic depolymerization for 4-8 times, and drying at 120° C. for 2-4 hours to obtain nano ZnO powder;

[0071] Step T3, allowing the silver nitrate solution to react with the alkali solution for 24 hours to obtain a nanosilver precursor;

[0072] Step T4, washing the nanosilver precursor prepared in step T3 with deionized water and ultrasonic depolymerization for 4-8 times, and drying at 00° C. for 4-8 hours to obtain a nanosilver precursor;

[0073] Step T5, mixing the nano ZnO powder obtained in step T2 with the nano silver precursor obtained in step T4, wherein the nano silver precursor accounts for 0.5-5%, grinding after mixing, and reacting at 500-800° C. for 2-6 hours, then cooling and grinding into ultrafine powder to form silver ion hybrid nano zinc oxide.

[0074] In order to improve the wear resistance, in the A component, the surface modified micropowder is preferably a mixture of polyethylene wax powder and polyfluorine modified wax powder, the weight fraction of the polyethylene wax powder in the surface modified micropowder is 50-80%, and the weight fraction of the polyfluorine modified wax powder in the surface modified micropowder is 20-50%. The surface modified micropowder improves the smoothness of the paint film and has a good effect on improving scratch resistance, wear resistance, and resistance to cosmetics wiping.

[0075] In order to improve the decorative effect, in the component A, the rheological additive is preferably a polyethylene wax with a transparency of more than 80%. The high-transparency polyethylene wax prevents powder sedimentation without significantly affecting the light transmittance and decorative effect of the paint film.

[0076] In order to improve the curing speed, in the B component, the mixed polyisocyanate curing agent is a mixture of HDI trimer and IPDI trimer, the weight fraction of the HDI trimer in the mixed polyisocyanate curing agent is 30-50%, and the weight fraction of the IPDI trimer in the mixed polyisocyanate curing agent is 50-80%. The HDI trimer and IPDI trimer mixed polyisocyanate curing agent can improve the curing speed and yellowing resistance, and the addition of IPDI trimer improves the hardness, chemical resistance and water resistance of the paint film.

[0077] In addition, the present invention also provides a method for preparing the above-mentioned automotive grade ultra-long durable antibacterial varnish.

[0078] The preparation method of component A is as follows:

[0079] Step S1, adding a mixed hydroxy resin, a mixed solvent, an additive, a nano antibacterial powder, a surface modified powder and a rheological additive in order according to a ratio, and stirring continuously for 5 minutes at a rotation speed of 200-400 rpm;

[0080] Step S2, grinding the mixed liquid stirred in step S1 by a nano sand mill for about 1 hour, the grinding medium particle size of the nano sand mill is 0.5 mm, and the fineness of the material after grinding is less than 10 μm;

[0081] Step S3, filtering the ground material in step S2 through a 400-mesh filter and then canning to obtain component A;

[0082] The preparation method of component B is as follows:

[0083] Add the mixed polyisocyanate curing agent and n-butyl acetate in order according to the ratio, and stir at a speed of 200-400 rpm for 10 minutes to obtain component B.

[0084] Furthermore, the present invention also provides an application of the above-mentioned automotive-grade ultra-long-lasting antibacterial varnish.

[0085] Add component B to component A in proportion, add the diluent of component C in proportion, spray it onto the surface of the object with an air spray gun, and dry it naturally for 7 days or bake it at 70℃ for 2 hours to completely cure, thereby obtaining an ultra-long-durable automotive-grade high-performance antibacterial coating.

[0086] Embodiment 1-5:

[0087] The following is a table of the contents of the components of the automotive-grade ultra-long-lasting antibacterial varnish of Examples 1-5, see Table 1.

[0088] Table 1

[0089]

[0090] Comparative Examples 1-3:

[0091] The following is a table of the contents of the various components of the varnishes of Comparative Examples 1-3, see Table 2.

[0092] Table 2

[0093] The varnishes of Examples 1-5 and Comparative Examples 1-3 were prepared by the preparation method described in the examples. The varnishes were sprayed into paint films by the application method of the examples. The formed paint films were tested for performance indicators. The tested performance indicators are shown in Table 3 below.

[0094] Table 3

[0095]

[0096] It can be seen from Table 3 above that the comparative example has poor adhesion and stone chip resistance without adding polyester resin and IPDI trimer curing agent; the comparative example has poor special dry grinding resistance and chemical performance without adding surface modification powder; the comparative example has poor light aging resistance without adding ultraviolet absorber, and the comparative example has greatly reduced antibacterial ability without adding nano antibacterial powder. Through the design and optimization of the formula, through Examples 1-5, we can find that the performance of the paint film is greatly improved, meeting the requirements of the automotive-grade long-lasting antibacterial varnish coating. Through comparison, it is found that polyester resin helps to improve the stone impact resistance (Example 1-2), and the surface modified micropowder helps to improve the wear resistance (Example 1-2). The appropriate amount of nano-antibacterial micropowder added greatly improves the antibacterial performance of the coating, and the antibacterial performance of the inorganic nano-antibacterial material used has no obvious attenuation after aging (Example 1-4), but too much addition will reduce the surface smoothness of the paint film (Example 4); the increase in the IPDI trimer content helps to improve the hardness, chemical resistance and scratch resistance of the coating (Example 2-3); a diluent system with a suitable volatilization gradient should be used. A diluent system that volatilizes too quickly can easily make the coating difficult to level, affecting the surface effect.

[0097] In addition, after the varnish prepared in Example 3 was sprayed into three groups of paint film coatings, two of the groups were subjected to high and low temperature aging and light aging treatments, respectively. Then, the antibacterial detection methods of GB / T21866-2008 and ISO21702:2019 were used to detect the antibacterial properties of the three groups of paint film coatings against Candida albicans, Escherichia coli, Staphylococcus aureus and human influenza A virus.

[0098] Among them, the concentration of bacterial solution is: Staphylococcus aureus 6.0×105CFU / mL; Candida albicans 9.9×105CFU / mL; Escherichia coli 7.6×105CFU / mL.

[0099] Test plate culture: Take 0.5mL of the test bacterial solution and drop it on the negative control sample (A), blank control sample (B) and antibacterial coating sample (C), respectively. Use sterile tweezers to pick up the sterile covering film and cover it on sample (A), sample (B) and sample (C), respectively, flatten it without bubbles, so that the bacteria are evenly in contact with the sample, place it in a sterile plate, and culture it at (37±1)℃ and relative humidity RH>90% for 24h. Perform 3 parallel tests for each sample.

[0100] Washing liquid culture: Take out the samples cultured for 24 hours, add 20mL of washing liquid respectively, wash sample (A), sample (B), sample (C) and the covering film (picked up with tweezers) repeatedly, shake well, take the washing liquid and inoculate it into nutrient agar medium (NA) according to GB / T4789.2, and culture at (37±1)℃ for 24 hours before counting the live bacteria.

[0101] Against human influenza A virus (H3N2): cytopathic assay;

[0102] The specific test results are shown in Tables 4 to 6, which are the antibacterial test results before aging, the antibacterial test results after high and low temperature aging, and the antibacterial test results after light aging.

[0103] Table 4. Antibacterial test results before aging

[0104]

[0105] Table 5. Antibacterial test results after high and low temperature aging

[0106]

[0107] Table 6. Antibacterial test results after light aging

[0108]

[0109] Depend on Figure 2-Figure 4 As can be seen from Tables 4 to 6, the automotive-grade ultra-long-lasting antibacterial varnish of the present invention has no obvious attenuation of antibacterial effect after 20 cycles of high and low temperature aging and more than 800 hours of light aging, and the killing rate of Escherichia coli, Staphylococcus aureus and Candida albicans is greater than 99.9%, showing super antibacterial performance.

[0110] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An automotive grade ultra-long durable antibacterial varnish, characterized in that: include: Component A, component B and component C, the ratio of component A, component B and component C is (A+B): C=1:0.4-0.7, where A:B=10:3; In parts by weight, the component A includes 66 parts of hydroxy acrylic resin, 6 parts of hydroxy polyester resin, 21.7 parts of mixed solvent, 0.5 parts of rheological additive, 1.5 parts of nano antibacterial powder, 1.5 parts of surface modified powder, 0.7 parts of leveling agent, 2 parts of anti-ultraviolet additive, 0.1 parts of drying agent, totaling 100 parts; In parts by weight, the B component includes 30 parts of HDI trimer, 50 parts of IPDI trimer, and 20 parts of n-butyl acetate, totaling 100 parts; The C component is a diluent, and by weight, the C component includes 10 parts of ethyl acetate, 20 parts of n-butyl acetate, 30 parts of propylene glycol methyl ether acetate, 30 parts of high boiling point aromatic solvent oil and 10 parts of mixed dibasic acid ester, totaling 100 parts; The nano antibacterial powder is silver ion hybridized nano zinc oxide, and the preparation method of the silver ion hybridized nano zinc oxide is as follows: Step T1, 7-15% Zn(NCS)2(C5H5N)2, 70-85% deionized water, 3-8% ammonia water and 0.5-1% supramolecular anchoring agent are mixed and reacted at 160-220°C for 4-12 hours to prepare nano ZnO by a hydrothermal method, wherein the supramolecular anchoring agent is a polyetheramine supramolecular anchoring agent; Step T2, washing the nano ZnO prepared in step T1 with deionized water and performing ultrasonic depolymerization for 4-8 times, and drying at 120° C. for 2-4 hours to obtain nano ZnO powder; Step T3, allowing the silver nitrate solution to react with the alkali solution for 24 hours to obtain a nanosilver precursor; Step T4, washing the nanosilver precursor prepared in step T3 with deionized water and ultrasonic depolymerization for 4-8 times, and drying at 80° C. for 4-8 hours to obtain a nanosilver precursor; Step T5, mixing the nano ZnO powder obtained in step T2 with the nano silver precursor obtained in step T4, wherein the nano silver precursor accounts for 0.5-5%, grinding after mixing, and reacting at 500-800° C. for 2-6 hours, then cooling and grinding into ultrafine powder to form silver ion hybrid nano zinc oxide.

2. The automotive grade ultra-long durable antibacterial varnish according to claim 1, characterized in that: In the component A, the mixed solvent is a mixture of n-butyl acetate, propylene glycol methyl ether acetate and ethylene glycol butyl ether acetate, the weight fraction of n-butyl acetate in the mixed solvent is 20-30%, the weight fraction of propylene glycol methyl ether acetate in the mixed solvent is 30-50%, and the weight fraction of ethylene glycol butyl ether acetate in the mixed solvent is 20-30%.

3. The automotive grade ultra-long durable antibacterial varnish according to claim 1, characterized in that: In the component A, the surface modified micropowder is a mixture of polyethylene wax powder and polyfluorine modified wax powder, the weight fraction of the polyethylene wax powder in the surface modified micropowder is 50-80%, and the weight fraction of the polyfluorine modified wax powder in the surface modified micropowder is 20-50%.

4. An application of the automotive-grade ultra-long-lasting antibacterial varnish according to any one of claims 1 to 3, characterized in that: Add component B to component A in proportion, add the diluent of component C in proportion, spray it onto the surface of the object with an air spray gun, and dry it naturally for 7 days or bake it at 70℃ for 2 hours to completely cure, thereby obtaining an ultra-long-durable automotive-grade high-performance antibacterial coating.

Citation Information

Patent Citations

  • Varnish coating for automobile body and application thereof

    CN111944412A

  • Varnish suitable for one-time spraying film formation of automobile body and preparation method thereof

    CN114806303A

  • Antibacterial paint for bullet train interior trimming as well as preparation method and application thereof

    CN108359369A